Maturation of Physalis peruviana L. seeds according to flowering and age of the fruit - Diniz, Fábio; Novembre, Ana Dionisia (Revista Ciência Agronômica, 2019)
It is important to understand the seed maturation process to determine the time point at which the seeds achieve optimum quality and the ideal time for harvest. This study aimed to study the maturation of Physalis peruviana L. seeds, based on flowering time and age of the fruit. This study was conducted from March to October of 2016 and 2017, in the city of Piracicaba, São Paulo. The plants were cultivated in four blocks using four stems, with spacing of 1.0 m between the plants and of 2.5 m between the rows. As experimental treatments, two flowering time points were defined: 55 and 105 days after transplanting (DAT); in each period, the flowers were marked at the anthesis and the respective fruits and seeds were evaluated at 45, 60, 75, and 90 days after anthesis (DAA). Characteristics during fruit development, such as age (days after anthesis) and changes in color, mass, and flavor, are parameters indicating the physiological maturity of fruits and seeds. The flowering time of the plant and the stage of fruit development influence the maturation of seeds, which present higher germination and vigor when obtained from fruits harvested at 75 DAA (55 DAT) and 60 DAA (105 DAT), after mass maturity.